Varnostna relevantnost kibernetskega prostora v obdobju Web 2.0 - Svete, Uroš (Sodobni vojaški izzivi, 2011)
Regardless if the information-communication technology has been developed to follow national security interests or not, at the moment, nobody doubts this correlation anymore. But the discussion has become much more important in time when practically all critical social infrastructures and processes depend on digital technology. In the paper, importance of the cyberspace has been analysed by security theories and with special focus on the Web 2.0 and WikiLeaks issue. The current way of such interactive communication is namely based on individuals as data and information producers, which could be in (Western) countries perceived as a greater challenge and in some cases even national security threat.
Keywords: Cyberspace; Informacijska tehnologija; Information technology; Kibernetski prostor; New technologies; Nove tehnologije; Safety; svetovni splet; Varnost; WikiLeaks